Recent progress on the design of hollow carbon spheres to host sulfur in room-temperature sodium-sulfur batteries 空心炭球在室温钠硫电池中的研究进展 - Yang, Jia Ying; Han, Hao Jie; Repich, Hlib; Zhi, Ri Cheng; Qu, Chang Zhen; Kong, Long; Kaskel, Stefan; Wang, Hong Qiang; Xu, Fei; Li, He Jun (New Carbon Materials, 2020)
Room-temperature sodium-sulfur (RT-Na/S) batteries are an important class of rechargeable batteries with a high theoretical capacity of 1 675 mAh g-1 and energy density up to 1 276 Wh kg-1 (based on Na2S). They are recognized as attractive next-generation high-energy-density devices for large-scale energy storage owing to the abundance and low cost of sodium and sulfur. However, similar to the working principle in lithium-sulfur batteries, they suffer from some basic problems such as the poor conductivity of elemental sulfur, a large volume change during charge-discharge cycling and a serious shuttle effect caused by sodium polysulfide dissolution. Moreover, the shuttle effect and volume change seem more pronounced in RT-Na/S batteries, which further decreases their performance and seriously hinders the progress towards their practical application. A fast growth in designing porous carbons, especially hollow carbon spheres (HCSs), as a sulfur host to address these problems has been seen in recent years, due to their unique structural features such as a large void space, a permeable shell, and simple functionalization. This review summarizes recent progress in HCS-based materials as the sulfur hosts in RT-Na/S batteries. Beginning with a brief introduction to RT-Na/S batteries, carbon hosts and design strategies for preparing HCSs, particular emphasis is placed on manipulating the pore structure, heteroatom doping and decoration with metal species with the aim of alleviating the "shuttle effect" and thus improving the performance. Finally, perspectives on current challenges and future research directions are discussed.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Hollow carbon spheres; Room-temperature sodium-sulfur batteries; Shuttle effect; Sulfur host materials